Reliability, Validity and Usefulness of 30–15 Intermittent Fitness Test in Female Soccer Players - Čović, Nedim; Jelešković, Eldin; Alić, Haris; Rađo, Izet; Kafedžić, Erduan; Sporiš, Goran; McMaster, Daniel T.; Milanović, Zoran (Frontiers in Physiology, 2016)
PURPOSE: The aim of this study was to examine the reliability, validity and usefulness of the 30-15IFT in competitive female soccer players. METHODS: Seventeen elite female soccer players participated in the study. A within subject test-retest study design was utilized to assess the reliability of the 30-15 intermittent fitness test (IFT). Seven days prior to 30-15IFT, subjects performed a continuous aerobic running test (CT) under laboratory conditions to assess the criterion validity of the 30-15IFT. End running velocity (VCT and VIFT), peak heart rate (HRpeak) and maximal oxygen consumption (VO2max) were collected and/or estimated for both tests. RESULTS: VIFT (ICC = 0.91; CV = 1.8%), HRpeak (ICC = 0.94; CV = 1.2%), and VO2max (ICC = 0.94; CV = 1.6%) obtained from the 30-15IFT were all deemed highly reliable (p>0.05). Pearson product moment correlations between the CT and 30-15IFT for VO2max, HRpeak and end running velocity were large (r = 0.67, p=0.013), very large (r = 0.77, p=0.02) and large (r = 0.57, p=0.042), respectively. CONCLUSION: Current findings suggest that the 30 -15IFT is a valid and reliable intermittent aerobic fitness test of elite female soccer players. The findings have also provided practitioners with evidence to support the accurate detection of meaningful individual changes in VIFT of 0.5 km/h (1 stage) and HRpeak of 2 bpm. This information may assist coaches in monitoring ‘real’ aerobic fitness changes to better inform training of female intermittent team sport athletes. Lastly, coaches could use the 30-15IFT as a practical alternative to laboratory based assessments to assess and monitor intermittent aerobic fitness changes in their athletes. Keywords: 30-15 intermittent fitness test, aerobic, cardiorespiratory fitness, intermittent activity, soccer, high intensity interval training.